Macrophages facilitate tumor cell PD‐L1 expression via an IL‐1β‐centered loop to attenuate immune checkpoint blockade - Cheng Xu; Yu Xia; Bai‐Wei Zhang; Emmanuel Kwateng Drokow; Hua‐Yi Li; Sen Xu; Zhen Wang; Si‐Yuan Wang; Ping Jin; Tian Fang; Xiao‐Ming Xiong; Pu Huang; et al. (MedComm)
Abstract Tumor‐associated macrophages (TAMs) play critical roles in reprogramming other immune cells and orchestrating antitumor immunity. However, the interplay between TAMs and tumor cells responsible for enhancing immune evasion remains insufficiently understood. Here, we revealed that interleukin (IL)‐1β was among the most abundant cytokines within the in vitro tumor‐macrophage coculture system, and enhanced IL‐1β expression was associated with impaired cytotoxicity of CD8+ T cells in human ovarian cancer, indicating the possibility that IL‐1β mediated immunosuppression during tumor‐TAMs crosstalk. Mechanistically, we demonstrated that IL‐1β significantly boosted programmed death‐ligand 1 (PD‐L1) expression in tumor cells via the activation of the nuclear factor‐κb signaling cascade. Specifically, IL‐1β released from TAMs was triggered by lactate, the anaerobic metabolite of tumor cells, in an inflammasome activation‐dependent manner. IL‐1β sustained and intensified immunosuppression by promoting C‐C motif chemokine ligand 2 secretion in tumor cells to fuel TAMs recruitment. Importantly, IL‐1β neutralizing antibody significantly curbed tumor growth and displayed synergistic antitumor efficacies with anti‐PD‐L1 antibody in tumor‐bearing mouse models. Together, this study presents an IL‐1β‐centered immunosuppressive loop between TAMs and tumor cells, highlighting IL‐1β as a candidate therapeutic target to reverse immunosuppression and potentiate immune checkpoint blockade.